2015
DOI: 10.1590/s0080-623420150000300012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported constipation in adults from the general population

Abstract: Objective: To estimate the prevalence of self-reported constipation and associated factors in the general population of a Brazilian city. Method: Secondary analysis of an epidemiological study, population-based, cross-sectional study, about bowel habits of Brazilian population. A total of 2,162 individuals were interviewed using two instruments: sociodemographic data and the adapted and validated Brazilian version of the "Bowel Function in the Community" tool. Results: There was a prevalence of 25.2% for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
2
19
0
2
Order By: Relevance
“…This study confirmed that constipation was reported to increase with age, which also accorded with previous observations [5, 9, 43, 4951]. As individuals aged, they might have difficulty in defecation.…”
Section: Discussionsupporting
confidence: 93%
“…This study confirmed that constipation was reported to increase with age, which also accorded with previous observations [5, 9, 43, 4951]. As individuals aged, they might have difficulty in defecation.…”
Section: Discussionsupporting
confidence: 93%
“…In defecation disorders, anorectal structural problems such as fissures, fistulas, and hemorrhoids may emerge due to the stress in the rectum (17). In a study, it was determined that hemorrhoids are the most common anal lesions in individuals with constipation (18). In our study, most common anorectal lesions in individuals were hemorrhoids and anal fissures, respectively.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies report that the prevalence rate of functional constipation ranges from 2.6% to 30.7% and the condition is more common in females and seniors [3]. In agreement with these data, Schmidt et al conducted an epidemiological study involving the Brazilian population and found a 25.2% rate of functional constipation among the individuals interviewed, with greater occurrences in the female gender and elderly population [3].…”
Section: Introductionmentioning
confidence: 62%
“…Functional constipation is an intestinal motility disorder that is highly prevalent throughout the world [1]. According to the Rome III Consensus, this condition is defined by two or more of the following criteria in a six-month period: fewer than three bowel movements per week, straining during defecation, hardened or fragmented stools, sensation of anorectal obstruction/blockage and the use of manual maneuvers to facilitate bowel movement [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation